A high-value recycling method for decommissioned photovoltaic modules based on chemical degradation
Patent Information
- Application Number
- CN202611178879.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-16
AI Technical Summary
(1)、机械处理法:通常包括破碎、筛分、研磨等,可以有效回收玻璃、铝框架等材料,但存在以下技术缺陷:材料彼此粘接,最终回收物的纯度较低,同时该方法对光伏组件中成本最高的高纯度硅电池片不能实现有效分离,后续还需复杂的筛选与提纯工艺,回收效率低下;(2)、热处理法:将光伏组件在空气或惰性气氛中进行加热,使光伏胶膜燃烧或软化,进而实现光伏组件层压件间剥离与分层
[0052] 1. This invention integrates pretreatment, solvent dissolution, chemical degradation, sorting, filtration separation, hydrometallurgical recovery, and solvent/catalytic system recycling into one system. It can systematically take into account multiple indicators such as the recovery of complete cover glass and silicon solar cells, high-purity recovery of metals such as silver, aluminum, and copper, acquisition of liquid hydrocarbon products, and closed-loop reuse of media, thus improving the problem of the disconnect between "decapsulation" and "high-value recovery" in the existing technology.
Smart Images

Figure CN122913182A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photovoltaic module recycling technology, and specifically to a high-value recycling method for retired photovoltaic modules based on chemical degradation. Background Technology
[0002] Photovoltaic power generation, as an important source of new energy, boasts advantages such as cleanliness, low carbon footprint, abundant resources, and wide applicability. The lifespan of photovoltaic modules is typically 20-25 years, and a large number of early-built photovoltaic power plants and their modules will enter their decommissioning phase in the coming years. According to a report by the International Renewable Energy Agency, my country will begin large-scale decommissioning of photovoltaic modules in 2025, reaching 1.5 million tons by 2030, and an estimated cumulative decommissioning volume of 74 million tons by 2050. With the continuous advancement of "dual-carbon" goals and the increasingly stringent requirements for efficient resource recycling, how to achieve efficient, high-value, and green recycling of all components of decommissioned photovoltaic modules has become an urgent problem to be solved.
[0003] Photovoltaic modules mainly consist of aluminum frames, junction boxes, solder strips, cover glass, photovoltaic encapsulant film, silicon solar cells, and backsheets. The most crucial part of a photovoltaic module is the laminated component, which removes the aluminum frame, junction box, and solder strips. This laminated component uses photovoltaic encapsulant film to tightly bond the glass, solar cells, and backsheet, forming a stable and weather-resistant composite structure. The effectiveness of the photovoltaic encapsulant film treatment directly determines whether the components of a decommissioned photovoltaic module can be efficiently disassembled and cleanly separated. It is a key factor affecting the overall component recovery rate, resource purity, process energy consumption, and economic efficiency.
[0004] Currently, the recycling of retired photovoltaic modules mainly adopts mechanical treatment, thermal treatment, chemical dissolution or a combination of these methods. (1) Mechanical treatment: usually includes crushing, screening, grinding, etc., which can effectively recycle materials such as glass and aluminum frames, but there are the following technical defects: the materials stick to each other, the purity of the final recycled material is low, and this method cannot effectively separate the high-purity silicon cells, which are the most expensive in photovoltaic modules, and a complex screening and purification process is required afterward, resulting in low recycling efficiency; (2) Thermal treatment: the photovoltaic module is heated in air or an inert atmosphere to burn or soften the photovoltaic film, thereby achieving the peeling and delamination between the laminates of the photovoltaic module. Although this method can recycle high-purity metals and silicon materials, it has the following technical defects: the process consumes a lot of energy and generates a lot of harmful gases and waste gas during pyrolysis, which also causes a lot of carbon emissions, harming the environment and human body. The gas generated during pyrolysis will also accumulate in the confined laminate, causing local high pressure and thus causing the cell to break, which is not conducive to the high-value recycling of silicon cells; (3) Chemical dissolution method: use organic solvents or acids and alkalis to soak the photovoltaic module, so that the photovoltaic film dissolves or swells, and then use mechanical force to separate the glass, silicon cells, backsheet, etc. to achieve a high recycling purity. However, it has the following technical defects: this method requires the use of a lot of toxic reagents to treat the photovoltaic module, generating a lot of waste liquid and high recycling cost; the laminate is tightly sealed, the solvent diffuses slowly in the photovoltaic film, the recycling time is long, the recycling efficiency is low, and the solvent will cause stress damage to the glass and cells when dissolving or swelling the photovoltaic film, reducing the recycling value of the photovoltaic module.
[0005] Addressing the common problems of poor treatment of photovoltaic encapsulant films and limited decapsulation effects in existing technologies for recycling retired photovoltaic modules, resulting in low recycling value, those skilled in the art have sought to develop a method that can systematically meet the requirements of decapsulation effect, component recovery value, low energy consumption and low emissions, solvent / medium recycling, and continuous process operation. For example, Chinese patent CN121423353A discloses a method for recovering silicon powder from waste photovoltaic panels. This method first disassembles and crushes the waste photovoltaic panels to obtain glass-containing silicon powder; then, through coarse selection, scavenging, and multiple fine flotation processes, the glass-containing silicon powder is mixed with modifiers, water, collectors, frothers, etc., to form a slurry, which is then aerated and floated to obtain high-purity silicon powder. The separation effect between glass and silicon powder can be controlled by a phosphate, water glass, and sulfuric acid water glass system. This method uses a small amount of environmentally friendly flotation reagents and recycles the flotation water. It can separate and purify glass and silicon powder within a short operating cycle, solving the problem of poor silicon recovery from waste photovoltaic panels. However, it has the following technical defects: it does not solve the recycling of components such as glass sheets, metals, and backsheets. It focuses more on the crushing and recycling of a single silicon component, which is not conducive to achieving high-value recycling of retired photovoltaic modules.
[0006] Chinese patent CN119566027A discloses a method and system for the resource recycling of photovoltaic modules. The method first mechanically disassembles the photovoltaic module to obtain the outer components and laminates. The laminates are then fed into a pyrolysis furnace for pyrolysis at 350-800℃ to obtain solid products, pyrolysis oil, and pyrolysis gas. The pyrolysis gas is purified and returned to the pyrolysis furnace as fuel. The pyrolysis solid products are then sorted to obtain solder ribbons, glass fragments, solar panel silicon wafers, and ash. The glass fragments are further melted in a high-temperature melting furnace at 1100-1800℃ to prepare glass fiber wool. The ash is then processed through acid washing, purification, and reduction to recover elemental silver and silicon powder. This method achieves the full-component recycling of waste photovoltaic panels. By using pyrolysis oil and pyrolysis gas as fuel, it reduces external energy consumption and improves the added value and comprehensive utilization rate of recycled glass. However, it has the following technical defects: its core technology is still based on medium- and high-temperature pyrolysis, and it requires additional multi-unit operations such as alkaline washing and deacidification, acid washing and leaching, and high-temperature fiberization. It is still insufficient for maintaining the integrity of silicon solar cells and achieving high-value recycling under low-carbon conditions.
[0007] Chinese patent CN118083997A discloses a process for recycling and reusing waste photovoltaic panels to manufacture silicon fertilizer. The method involves disassembling waste crystalline silicon photovoltaic panels, dividing and crushing the laminated components, and immersing them in an organic solvent for interlayer particle separation. The system is then separated into solid and liquid phases, and the clarified organic solvent is recovered and recycled. The separated mixture is then subjected to alcohol washing, water washing, vacuum drying, and air separation to obtain backsheets, solar cells, and glass particles. The glass particles are further mixed with sodium carbonate and calcined at 1050-2000℃ to produce sodium silicate, which is then used to prepare silicon fertilizer or a sand control binder. This method initially achieves solvent recovery and the recycling and reuse of glass and backsheets, but it has the following technical shortcomings: it still does not solve problems related to the protection of intact solar cells, high-value metal recovery, and plastic recycling.
[0008] As can be seen from the above-mentioned patents, the existing technology for recycling retired photovoltaic modules has the following technical defects: it is limited to the optimization of a certain local link or a certain specific component, and has problems such as insufficient raw material adaptability, complex process flow, disconnect between decapsulation and high-value recycling, high system energy consumption or heavy burden of waste liquid and waste gas treatment. It fails to fundamentally solve the core challenges faced by photovoltaic modules in the process of high-value recycling of all components.
[0009] Therefore, designing a high-value recycling method for retired photovoltaic modules based on chemical degradation that can overcome the above limitations, completely recover silicon solar cells and glass plates through chemical degradation of photovoltaic encapsulant film, recover metal components at high value, and take into account low energy consumption, low emissions, high efficiency, and continuous closed-loop operation throughout the entire process has become an urgent problem to be solved. Summary of the Invention
[0010] To address the problems existing in the prior art, this invention provides a high-value recycling method for decommissioned photovoltaic modules based on chemical degradation, thereby solving at least one of the aforementioned technical problems.
[0011] The technical solution of this invention is: a high-value recycling method for decommissioned photovoltaic modules based on chemical degradation, comprising the following steps:
[0012] S1. Pre-treatment of decommissioned photovoltaic panels:
[0013] Dismantle, clean and sort retired photovoltaic modules to remove directly recyclable parts and obtain photovoltaic laminates. Directly recyclable parts include aluminum frames, junction boxes or wiring frames.
[0014] S2, Chemical degradation of photovoltaic film:
[0015] The photovoltaic laminate is fixed to the limiting device at the bottom of the reactor. A mixed solution of solvent and catalyst is added to the reactor. Under the action of a dynamic fluid circulation system, the solution is dissolved and catalytically degraded at room temperature to 200°C and 0.1MPa to 5MPa for 0.1 to 8 hours to obtain a complete cover glass, silicon solar cell, liquid hydrocarbon product and a reaction mixture containing solvent, catalyst and soluble metal components.
[0016] S3, Sorting:
[0017] The reaction products were sorted, and the glass plate and silicon solar cell were removed. After cleaning and vacuum drying, reusable cover glass and silicon solar cell were obtained.
[0018] S4, Filtration and Separation:
[0019] The heterogeneous mixture is separated to remove solid impurities and undissolved particles, and the metal concentrates or metal leachates of silver, aluminum, copper and solder are recovered. The reaction mixture is allowed to stand at 20℃~90℃ to separate into layers, yielding an organic phase and an ionic liquid phase or an acidic catalytic phase. The organic phase is desolventized and then distilled to obtain a liquid hydrocarbon component. The metal concentrates or metal leachates are separated by hydrometallurgical methods, and then subjected to filtration to remove impurities, selective precipitation and / or electrolysis to obtain high-purity silver, high-purity aluminum and high-purity copper.
[0020] S5, Solvent recycling and catalytic system regeneration:
[0021] The removed solvent is returned to step S2 for recycling; the ionic liquid phase or acidic catalytic phase is regenerated and then returned to step S2 for recycling.
[0022] This invention integrates pretreatment, solvent dissolution, chemical degradation, sorting, filtration separation, hydrometallurgical recovery, and solvent / catalytic system recycling into one system. It can systematically take into account multiple indicators such as the recovery of complete cover glass and silicon solar cells, high-purity recovery of metals such as silver, aluminum, and copper, acquisition of liquid hydrocarbon products, and closed-loop reuse of media, thus improving the problem of the disconnect between "decapsulation" and "high-value recovery" in the prior art.
[0023] Furthermore, the disassembly in step S1 is carried out manually or by automated disassembly equipment. The automated disassembly equipment includes a frame removal unit, a junction box cutting unit, an appearance identification unit, and a laminate conveying unit. According to the component size and reactor specifications, the photovoltaic laminate after removing the frame is placed directly on the bottom limiting device of the reactor as a whole, or cut into laminate sheets of 10mm×10mm~2000mm×2000mm. The cleaning process adopts a combination of water washing and organic solvent washing to remove surface mud, dust, oil stains and residual adhesive on the back.
[0024] Furthermore, the solvent in step S2 is selected individually or in combination based on the photovoltaic film type, degree of crosslinking, and backsheet configuration; the solvent includes one or more of aromatic hydrocarbon solvents, alicyclic hydrocarbon solvents, halogenated hydrocarbon solvents, terpene solvents, ether solvents, alcohol solvents, ketone solvents, supercritical alkane solvents, inorganic acid solvents, and oxidizing mixed reagents; optional solvents include toluene, xylene, mixed xylene, cyclohexane, n-heptane, light naphtha, trichloroethylene, o-dichlorobenzene, tetrahydrofuran, d-limonene, benzyl alcohol, anisole, dimethylcyclohexylamine, isopropanol, supercritical isopentane, nitric acid, concentrated sulfuric acid, and a mixture of hydrofluoric acid and hydrogen peroxide, etc.
[0025] The solvent can be selected based on the solubility parameter matching relationship between the photovoltaic film and the solvent. For EVA films, one or more of toluene, xylene, mixed xylene, trichloroethylene, o-dichlorobenzene, and d-limonene are preferred. For POE films, tetrahydrofuran, dimethylcyclohexylamine, a mixture of d-limonene and aromatic hydrocarbons, or a supercritical alkane and organic co-solvent system are preferred. For EVA / POE co-extruded films and encapsulation layers after long-term service aging, a mixture of terpenes / aromatic hydrocarbons, aromatic hydrocarbons / alcohols, or ethers / aromatic hydrocarbons is preferred. For photovoltaic laminates that require simultaneous promotion of metal grid line dissolution or removal of difficult-to-treat backsheets, nitric acid or concentrated sulfuric acid can be added to the above organic solvent systems, or a mixture of hydrofluoric acid and hydrogen peroxide can be used in the staged treatment to improve the degradation efficiency of the photovoltaic film and the leaching efficiency of metal components.
[0026] Furthermore, an inorganic solvent is added in step S2. The inorganic solvent is used by adding it as a whole, adding it in stages, or selectively leaching it later. When the target is to recover the complete cover glass, the inorganic solvent is used to leach the silicon solar cells or metal concentrates after the glass plate is removed. When the target is to rapidly dissolve metals, the inorganic solvent is added in the later stage of the reaction in step S2 by spraying or circulating it, thereby promoting the deadhesion of the film interface and allowing metals such as silver, aluminum, and copper to enter the liquid phase.
[0027] The reactor is a rectangular or near-rectangular pressure-resistant reactor, operating in conjunction with a dynamic circulating spray system. The dynamic circulating spray system includes a collection zone, a filter, a circulating pump, and spray devices. The spray devices include a bottom manifold at the bottom of the reactor, a top manifold at the top of the reactor, and nozzles at the outlet of the top manifold. The bottom manifold is connected to the circulating pump and the top manifold sequentially through the filter. The reactor shell can be made of 316L stainless steel, Hastelloy, or other corrosion-resistant alloy materials. The inner wall of the reactor is lined with polytetrafluoroethylene (PTFE) and equipped with jacketed heating, pressure monitoring, and inert gas protection devices. When processing solid laminated components after removing the frame and junction box, the reactor volume is preferably 0.01-6 m³. 3 The initial liquid volume of the corresponding mixed solution is preferably 1L~3000L; a limiting and fixing device is set at the bottom of the inner side of the reactor, which includes a buckle, a pressure strip, a positioning pin, and a guide frame, used to fix the photovoltaic laminate after the aluminum frame, junction box, or junction frame has been removed; the dynamic circulating spray system first introduces the solvent / ionic liquid mixture collected at the bottom of the reactor into the filter to remove metal fragments, weld strips, and incompletely separated particles, and then transports it to the nozzles on the upper layer of the reactor through the circulating pump and the top manifold, thereby forming a continuously renewed solvent / catalyst liquid film on the surface of the photovoltaic laminate to achieve mass transfer, heat transfer, and stirring.
[0028] Furthermore, the spraying device can be arranged above, to the side, or in a combined upper and lower position on the laminate; the circulation flow rate can be adjusted according to the projected area of the laminate, the number of nozzles, and the liquid volume; when using a 2m... 3 When processing whole-plate laminates using a cuboid pressure-resistant reactor, the preferred circulation flow rate is 200~400 L / min, and the spray pressure is 0.05~0.8 MPa. By adjusting the nozzle angle, flow rate, spray coverage, and the distance between the laminate and the nozzle, the organic solvent and catalyst can flow uniformly at the interfaces of glass / film, cell / film, and film / backsheet, thereby promoting full swelling and catalytic degradation of the film and reducing the risk of glass cracking and cell breakage caused by localized excessive expansion.
[0029] Furthermore, the sorting in step S3 can be completed by various methods such as manual sorting and mechanical clamping; for the obtained complete cover glass and complete silicon solar cell, anhydrous ethanol, isopropanol, n-hexane or a mixture thereof can be used for spray cleaning to remove residual organic matter and catalyst; then, vacuum drying at 40℃~90℃ for 0.5~6h is performed to obtain the recycled components that can be directly entered into the subsequent remanufacturing or material reuse stages.
[0030] Further, the catalyst in step S2 is an ionic liquid catalyst, a eutectic solvent catalyst, and / or an acidic catalyst; the ionic liquid catalyst is obtained by mixing a cationic reagent and anionic reagent in a molar ratio of 1:(0.5~7); the amount of ionic liquid catalyst is 1%~50% of the organic encapsulant mass in the photovoltaic laminate, preferably 5%~20%; the acidic catalyst is added at 0.5%~20% of the mass of the mixed solution, preferably 1%~10%; the catalyst can be prepared in advance before the reaction, or it can be generated in situ in the reactor or added in stages.
[0031] Furthermore, the cation reagent is one or more of imidazole salts, pyridine salts, quaternary ammonium salts, and quaternary phosphine salts; imidazole salts include 1-butyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium chloride, 1-propyl-3-methylimidazolium chloride, and 1-octyl-3-methylimidazolium chloride; pyridine salts include benzylpyridine salt and butylpyridine salt; quaternary ammonium salts include triethylammonium chloride, tetraethylammonium salt, benzyltrimethylammonium salt, and tetrabutylammonium salt; and quaternary phosphine salts include trioctylmethylphosphine salt.
[0032] Furthermore, the anionic reagent is one or more of a metal halide, a metal halide, or a fluorosulfonate; the metal halide includes anhydrous aluminum trichloride, anhydrous ferric chloride, cuprous chloride, gallium trichloride, and stannous chloride; the metal halide includes zinc chloride, sodium tetrafluoroborate, lithium hexafluorophosphate, potassium hexafluorophosphate, and potassium hexafluoroantimonate; and the fluorosulfonate includes sodium trifluoromethanesulfonate.
[0033] Furthermore, the cationic reagent is 1-butyl-3-methylimidazolium chloride [Bmim]Cl, and the anionic reagents are anhydrous aluminum chloride and sodium trifluoromethanesulfonate. These three are combined in a molar ratio of 4:5:1 to form an ionic liquid catalytic system possessing both Lewis and Brønsted acid sites. In this system, the aluminochlorochlorophosphate species provides strong Lewis acidity, which is beneficial for polymer chain activation and the loosening of cross-linked structures; the fluorosulfonate group helps stabilize the protonated acid sites in the system, thereby promoting the deacetylation of vinyl acetate units in EVA, the activation of polar groups in the aged film, and subsequent chain scission processes.
[0034] For EVA encapsulation films, the Lewis acid-Brønsted acid synergistic system can promote the activation of ortho-C-C bonds in ester groups, the removal of vinyl acetate units, and the relaxation of crosslinking networks, gradually transforming the film from a highly adhesive solid into a flowable, extractable oligomer or liquid hydrocarbon precursor. For aged EVA films, ionic liquids can also weaken the highly crosslinked regions formed after photo-aging and thermo-oxidative aging at lower temperatures, improving the de-adhesion efficiency at the glass-cell interface.
[0035] For POE or EVA / POE co-extruded films, Lewis acid sites can promote the activation, isomerization, and β-cleavage of polyolefin segments, and increase solvent penetration rate under dynamic cyclic spraying. For fluorinated backsheets, PET backsheets, or laminates with long service lives, interfacial mass transfer can be enhanced by increasing the proportion of polar components in the mixed solvent or by increasing the reaction temperature and circulation flow rate. The above mechanism description is for the purpose of helping to understand the present invention and does not limit the scope of protection of the present invention. The preferred reaction conditions are room temperature to 160°C, 0.1 MPa to 2.5 MPa, and 0.5 to 10 h.
[0036] Furthermore, the acid catalyst is one or more of concentrated sulfuric acid, trifluoromethanesulfonic acid, methanesulfonic acid, p-toluenesulfonic acid, and chlorosulfonic acid. The acid catalyst can be used alone or in combination with an ionic liquid catalyst. Concentrated sulfuric acid can promote the deacetylation of vinyl acetate units and the loosening of cross-linked networks in EVA, while trifluoromethanesulfonic acid, as a strong Brønsted acid, can increase the activation rate of polar groups in the aged film. Both are beneficial to the chain scission degradation and interfacial deadhesion of the photovoltaic film. The reaction conditions are 40℃~170℃, 0.1MPa~2.5MPa, and 0.5~10h.
[0037] Furthermore, the catalyst further includes a eutectic solvent catalyst, which is a eutectic system (also known as a deep eutectic solvent) composed of an amide compound and a chloroaluminate; the amide compound refers to an organic compound containing an amide group (–CONH–) in its molecule, selected from one or more of acetamide, propionamide, butyramide, hexamethylenetetramine, benzamide, nicotinamide, urea, caprolactam, and N-methylacetamide; preferably acetamide, propionamide, urea, or caprolactam; more preferably acetamide; the chloroaluminate is provided by anhydrous aluminum trichloride, or formed by anhydrous aluminum trichloride and a chlorine donor to form a chloroaluminate anion; the chlorine donor is preferably one or more of choline chloride, ammonium chloride, potassium chloride, and sodium chloride. Preferably, the molar ratio of the amide compound to anhydrous aluminum trichloride is 1:(0.5~3), more preferably 1:(1~2); when a chlorine donor is used in the compound, the molar ratio of the amide compound, anhydrous aluminum trichloride, and the chlorine donor is preferably 1:(0.5~3):(0.01~1); the amount of the eutectic solvent catalyst, based on the mass of the organic encapsulant in the photovoltaic laminate, is 1%~50%, preferably 5%~30%; the eutectic solvent catalyst can be prepared in advance and added to the reaction system, or the amide compound and anhydrous aluminum trichloride can be added to the reactor separately or together to generate a eutectic phase in situ; anhydrous aluminum trichloride or amide compound can also be added in stages according to the reaction process to maintain catalytic activity and solvent characteristics.
[0038] Furthermore, in step S4, the solvent removal and distillation pressure of the organic phase is 0.01~0.08 MPa, and the distillation temperature is 60℃~220℃. Depending on the intended use of the target product, the liquid hydrocarbon can be cut into C5~C12 light fractions, C13~C18 medium fractions, and C19+ heavy fractions. The light fractions are used as components for blending recycled gasoline, the medium fractions are used as precursor components for diesel or sustainable aviation fuel, and the heavy fractions are returned to the cracking unit or used as chemical feedstocks. Alternatively, it can be returned to step S2 to replenish the organic solvent.
[0039] In step S4, the solid residue obtained by filtration, sedimentation, or centrifugation includes solder ribbon fragments, silver paste strips, aluminum backing fragments, copper strips, backing plate particles, and inorganic fine particles. This part can be further screened, magnetically separated, eddy current separated, and subjected to necessary selective leaching to obtain silver, aluminum, copper, and solder metal enrichments. For the metals that enter the liquid phase, a hydrometallurgical method can be used for recovery: first, selective leaching is carried out using nitric acid, concentrated sulfuric acid, sulfuric acid / iron salt system, or a mixture of hydrofluoric acid and hydrogen peroxide; then, impurities are removed by plate and frame filtration or membrane filtration; and finally, high-purity silver, high-purity aluminum, and high-purity copper are obtained through selective precipitation, displacement, electrolysis, or ion exchange.
[0040] The mixture obtained after the catalytic degradation reaction contains liquid hydrocarbon products, solvent, ionic liquid catalyst and a small amount of suspended solids. After standing at 20℃~60℃ for 0.1~5h, the system usually forms an upper organic phase and a lower ionic liquid phase. If necessary, an intermediate transition phase may also be formed. The quality of the clear liquid can be further improved by hot filtration, centrifugation or demulsification. The organic phase after solvent removal can be purified by vacuum distillation to obtain narrow boiling range liquid hydrocarbon components.
[0041] When the system uses inorganic acid or a mixed reagent containing hydrogen peroxide, the acidic liquid phase obtained by phase separation can be directly introduced into the metal recovery unit as a metal leaching solution without the need for additional liquid replacement. After filtering out silicon powder, glass powder and backplate particles, selective precipitation, electrolysis or crystallization recovery can be carried out in sequence according to the standard potential difference of silver, aluminum and copper.
[0042] Furthermore, the regeneration in step S5 includes one or more of the following combinations: pre-devouring, acidity recovery, and impurity removal;
[0043] Pre-devouring is the process of removing residual solvents and low-boiling organics from the ionic liquid phase under reduced pressure and / or inert gas protection.
[0044] Acidity recovery involves adding metal halides, fluorosulfonate salts, or organic halides to the pre-devoured ionic liquid system to restore Lewis acidity and Brønsted acid sites.
[0045] Impurity removal involves removing coke particles, inorganic particles, and polar byproducts through filtration separation and / or adsorption purification.
[0046] The "regeneration" mentioned in step S5 refers to restoring the acidity distribution and structural stability of the ionic liquid catalyst through physical and chemical means, while simultaneously achieving the recycling of solvent and ionic liquid, reducing the amount of fresh solvent and catalyst replenishment. Preferably, the ionic liquid enriched phase obtained from phase separation in step S4 is introduced into a regeneration reactor equipped with a jacketed heating system, a vacuum system, and an inert gas protection interface. Pre-devouring is performed at 60℃~120℃ and 0.01~0.05MPa for 1~6 hours to remove residual solvent and low-boiling organic matter.
[0047] When the acidity of the ionic liquid system decreases due to changes in complexation equilibrium, hydrolysis, or consumption of acid sites during the reaction, anhydrous aluminum trichloride, zinc chloride, sodium trifluoromethanesulfonate, or a small amount of organic halogenated compounds can be added according to the system composition. The addition operation is preferably carried out at 60℃~120℃, followed by stirring for 0.5~3h to allow the newly added components to fully recombine and complex with the ionic liquid, restoring catalytic activity.
[0048] The regenerated ionic liquid can be thermally filtered at 40℃~80℃ through a 1~20μm sintered metal filter or ceramic filter to remove coke particles and inorganic particles; if necessary, it can be further passed through an activated clay, alumina, or molecular sieve adsorption column to remove trace water and polar byproducts; ionic liquids that meet the acidity and activity requirements can be directly returned to step S2 for recycling; the total reuse rate of the recovered solvent and regenerated ionic liquid during the recycling process is preferably not less than 85%, more preferably not less than 90%;
[0049] When concentrated sulfuric acid, trifluoromethanesulfonic acid or other acidic catalysts are used, regeneration may include removing organic solvents, adjusting acidity, adding oxidants and removing impurities. In the case of sulfuric acid system, hydrogen peroxide or iron salts can be added to restore oxidizing properties. In the case of trifluoromethanesulfonic acid system, low-boiling components can be removed by vacuum devolatilization and then directly reused or fresh trifluoromethanesulfonic acid can be added. The total reuse rate of acidic catalyst phase is preferably not less than 80%.
[0050] This invention enables the synergistic high-value recovery of glass, silicon cells, metals, and organic encapsulants from decommissioned photovoltaic modules without employing a pyrolysis route. After analysis confirms that the catalyst meets the usage requirements, the regenerated catalyst can be returned directly or after appropriate dilution to step S2 to participate in the next cycle reaction, thereby constructing a continuous, closed-loop recovery process.
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] 1. This invention integrates pretreatment, solvent dissolution, chemical degradation, sorting, filtration separation, hydrometallurgical recovery, and solvent / catalytic system recycling into one system. It can systematically take into account multiple indicators such as the recovery of complete cover glass and silicon solar cells, high-purity recovery of metals such as silver, aluminum, and copper, acquisition of liquid hydrocarbon products, and closed-loop reuse of media, thus improving the problem of the disconnect between "decapsulation" and "high-value recovery" in the existing technology.
[0053] 2. This invention, through the synergistic effect of a rectangular pressure-resistant reactor and a dynamic circulating spray system, can still improve the renewal speed and penetration uniformity of solvent and catalyst on the surface of laminated components without the presence of a stirring paddle in the reactor, shorten the encapsulant film treatment cycle, and reduce the risk of damage to glass and solar cells caused by local excessive swelling, thereby facilitating the gentle and efficient dismantling of retired photovoltaic modules.
[0054] 3. This invention, through the integrated design of reaction mixture phase separation, solvent removal, liquid hydrocarbon distillation, and regeneration of ionic liquid phase or acidic catalytic phase, enables the solvent and catalytic system to be recycled multiple times, reducing the burden of waste liquid and waste gas treatment, lowering process operating costs, and providing an feasible technical path for the low-carbon and high-value recycling of retired photovoltaic modules. Attached Figure Description
[0055] Figure 1This is a flowchart illustrating the high-value recycling of decommissioned photovoltaic modules based on chemical degradation, as described in this invention.
[0056] Figure 2 This is a perspective view of the high-value recycling device for retired photovoltaic modules according to the present invention.
[0057] Figure 3 This is a schematic diagram of the internal structure of the high-value recycling device for retired photovoltaic modules of the present invention.
[0058] Figure 4 This is a schematic diagram illustrating the chemical degradation effect of the present invention on EVA film.
[0059] Figure 5 This is a schematic diagram illustrating the chemical degradation effect of the POE film according to the present invention.
[0060] Figure 6 This is a list of recycling conditions and key recycling indicators for retired photovoltaic modules according to Embodiments 1-12 of the present invention.
[0061] In the diagram: 1. Reactor; 2. Nozzle; 3. Top manifold; 4. Bottom manifold; 5. Filter; 6. Circulation pump; 7. Sealing cap; 8. Guide frame; 9. Buckle; 10. PTFE liner; 11. Photovoltaic laminate; 12. Positioning pin; 13. Photovoltaic laminate load-bearing block; 14. Guide frame load-bearing block. Detailed Implementation
[0062] The present invention will now be further described with reference to the accompanying drawings.
[0063] See Figure 1-6 The structures, proportions, and sizes illustrated in the accompanying drawings are merely for illustrative purposes and to aid those skilled in the art in understanding and reading the invention. They are not intended to limit the scope of the invention and therefore have no substantial technical significance. Any modifications to the structure, changes in proportions, or adjustments to size, without affecting the effectiveness and purpose of the invention, should still fall within the scope of the technical content disclosed in this invention. Furthermore, the terms "upper," "lower," "left," "right," "middle," and "one" used in this specification are merely for clarity and not intended to limit the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the invention's implementation.
[0064] Example 1: A high-value recycling method for decommissioned photovoltaic modules based on chemical degradation, referenced Figure 1 It includes the following steps:
[0065] S1. Pre-treatment of retired photovoltaic panels: Take retired single-glass crystalline silicon photovoltaic modules, the main encapsulating film of the modules is EVA; firstly, manually remove the aluminum frame and junction box, retaining the whole laminate with a size of approximately 1956mm×991mm, remove surface dust with 40℃ deionized water and brushing, then spray with 95% ethanol and dry under 60℃ hot air to obtain photovoltaic laminate 11;
[0066] S2, Chemical degradation of photovoltaic film: The photovoltaic laminate 11 is fixed in a 2m³ volume using bottom clips. 3 Inside a rectangular pressure-resistant reactor, the shell of reactor 1 is made of alloy material and lined with PTFE; 160L of mixed xylene and 1920g of ionic liquid catalyst are added, the ionic liquid catalyst being prepared by mixing [Bmim]Cl, AlCl3 and NaOTf in a molar ratio of 4:5:1; a dynamic circulating spray system is activated, so that the mixed solution collected at the bottom of the reactor is first filtered by an online filter device and then transported to the upper nozzle by a circulating pump. The reaction is carried out for 3 hours at a circulating flow rate of 320L / min, a spray pressure of 0.15MPa~1.2MPa, and 140℃ to obtain a complete cover glass, silicon solar cells, liquid hydrocarbon products and reaction mixture;
[0067] S3. Sorting: After the reaction is completed, open the reactor, release the bottom limit and manually pick up the complete cover glass and silicon solar cell, spray them with anhydrous ethanol and rinse them with n-hexane in sequence, and vacuum dry them at 60℃ and 0.03MPa for 2 hours to obtain reusable cover glass and silicon solar cell.
[0068] S4. Filtration and Separation: The remaining reaction mixture is thermally filtered through a 20μm ceramic membrane to obtain a metal-enriched residue and a filtrate. The metal-enriched residue is added to 0.5mol / L nitric acid and leached at 80℃ for 1.5h. After filtration to remove backplate particles and inorganic fine particles, sodium chloride solution is first added to the filtrate to precipitate and recover silver. Then, the mother liquor is electrolyzed and precipitated to obtain high-purity silver, high-purity copper, and high-purity aluminum. The filtrate is allowed to stand at 40℃ for 1h to separate into two layers, resulting in an upper organic phase and a lower ionic liquid phase. After desolvation under reduced pressure, the organic phase is distilled at 0.05MPa and 80℃~180℃ to obtain a liquid hydrocarbon component.
[0069] S5. Solvent recycling and catalytic system regeneration: The mixed xylene recovered in step S4 is returned to step S2 for recycling; the ionic liquid phase is first pre-devoured at 90℃ and 0.03MPa for 2h, then 5wt% anhydrous aluminum trichloride and 1wt% sodium trifluoromethanesulfonate are added, and after filtration through a 5μm filter, it is returned to step S2 for recycling.
[0070] In this embodiment, the liquid hydrocarbon yield is approximately 62.3 wt%, and the recovery rates of silver, aluminum, and copper are approximately 96.2%, 90.8%, and 92.4%, respectively.
[0071] The solvent and ionic liquid of Example 1 were continuously recycled 5 times. On the 5th cycle, the integrity recovery rate of the cover glass was still higher than 96%, the integrity recovery rate of the battery cell was still higher than 90%, and the liquid hydrocarbon yield was still higher than 59 wt%, indicating that the method of the present invention has good medium cycling stability.
[0072] Example 2: A method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation, comprising the following steps:
[0073] S1. Pre-treatment of retired photovoltaic panels: Take retired single-glass crystalline silicon photovoltaic modules with EVA as the main encapsulating film. First, manually remove the aluminum frame and junction box, leaving the whole laminate with a size of approximately 1956mm×991mm. Remove surface dust with 40℃ deionized water and brushing. Then, spray with 95% ethanol and dry under 60℃ hot air to obtain photovoltaic laminate 11.
[0074] S2, Chemical degradation of photovoltaic film: To a volume of 2m³ 3 A photovoltaic laminate 11, which is fixed by a bottom snap-fit, is installed in a rectangular pressure reactor 1. The shell of the reactor 1 is made of alloy material and lined with PTFE. 160L of toluene and 1600g of ionic liquid catalyst are added. The ionic liquid catalyst is prepared by mixing [Bmim]Cl and AlCl3 in a molar ratio of 1:1.2. The dynamic circulation spray system is turned on so that the mixed solution collected at the bottom of the reactor is first filtered by an online filter and then transported to the upper nozzle by a circulation pump. The reaction is carried out at 135℃ and 1.0MPa for 4h under the condition of circulation flow rate of 240L / min.
[0075] S3. Sorting: After the reaction is completed, open the reactor, release the bottom limit and manually pick up the complete cover glass and silicon solar cell, spray them with anhydrous ethanol and rinse them with n-hexane in sequence, and vacuum dry them at 60℃ and 0.03MPa for 2 hours to obtain reusable cover glass and silicon solar cell.
[0076] S4. Filtration and separation: The reaction mixture was filtered through a 20μm stainless steel sintered mesh to obtain a metal concentrate and filtrate, which were then allowed to stand at 35℃ for 1 hour to separate into layers. The metal concentrate was subjected to selective leaching with nitric acid, silver precipitation with sodium chloride, copper recovery by electrolysis, and pH adjustment to precipitate aluminum to obtain high-purity silver, high-purity copper, and high-purity aluminum. After removing toluene from the organic phase, the liquid hydrocarbon component was obtained by distillation at 0.05MPa and 90℃~170℃.
[0077] S5. Solvent recycling and catalytic system regeneration: The toluene recovered in step S4 is returned to step S2 for recycling; the ionic liquid phase is pre-devoured at 95℃ and 0.03MPa for 2.5h, and a small amount of anhydrous aluminum trichloride is added before returning to step S2 for recycling.
[0078] In this embodiment, the liquid hydrocarbon yield was approximately 58.7 wt%, and the recovery rates of silver, aluminum, and copper were approximately 94.8%, 89.6%, and 91.3%, respectively.
[0079] Example 3: A method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation, comprising the following steps:
[0080] S1. Pre-treatment of retired photovoltaic panels: Take retired single-glass crystalline silicon photovoltaic modules with EVA as the main encapsulating film. First, manually remove the aluminum frame and junction box, leaving the whole laminate with a size of approximately 1956mm×991mm. Remove surface dust with 40℃ deionized water and brushing. Then, spray with 95% ethanol and dry under 60℃ hot air to obtain photovoltaic laminate 11.
[0081] S2, Chemical degradation of photovoltaic film: To a volume of 2m³ 3 A rectangular pressure-resistant reactor 1 is fitted with a photovoltaic laminate 11 that is fixed by a bottom snap-fit. The shell of the reactor 1 is made of alloy material and lined with PTFE. 120L of d-limonene, 40L of mixed xylene and 1920g of ionic liquid catalyst are added. The ionic liquid catalyst is prepared by mixing [Bmim]Cl, AlCl3 and NaOTf in a molar ratio of 3:4:1. The dynamic circulation spray system is turned on so that the mixed solution collected at the bottom of the reactor is first filtered by an online filter and then transported to the upper nozzle by a circulation pump. The reaction is carried out at 145℃ and 1.3MPa for 2.5h under the condition of circulation flow rate of 320L / min.
[0082] S3. Sorting: After the reaction is completed, open the reactor, release the bottom limit and manually pick up the complete cover glass and silicon solar cell, spray them with anhydrous ethanol and rinse them with n-hexane in sequence, and vacuum dry them at 60℃ and 0.03MPa for 2 hours to obtain reusable cover glass and silicon solar cell.
[0083] S4. Filtration and separation: The reaction mixture is hot filtered and then allowed to stand at 40℃ for 0.5h to separate into layers; the metal concentrate obtained by filtration is leached with nitric acid, precipitated and electrolyzed to obtain high-purity silver, high-purity copper and high-purity aluminum; the organic phase is desolventized and then distilled at 0.04MPa and 85℃~185℃ to obtain liquid hydrocarbon components.
[0084] S5. Solvent recycling and catalytic system regeneration: The d-limonene and mixed xylene recovered in step S4 are returned to step S2 for use; the ionic liquid phase is devolatilized at 90℃ and 0.02MPa and then purified by an alumina adsorption column before being recycled.
[0085] In this embodiment, the liquid hydrocarbon yield is approximately 65.2 wt%, and the recovery rates of silver, aluminum, and copper are approximately 96.9%, 91.7%, and 93.1%, respectively.
[0086] Example 4: A method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation, comprising the following steps:
[0087] S1. Pre-treatment of retired photovoltaic panels: Take retired double-glass crystalline silicon photovoltaic modules with POE as the main encapsulating film. After disassembly, retain the whole laminate with a size of approximately 1956mm×991mm and including front and rear glass. Remove surface dust with 40℃ deionized water and brushing. Then spray with 95% ethanol and dry under 60℃ hot air to obtain photovoltaic laminate 11.
[0088] S2, Chemical degradation of photovoltaic film: To a volume of 2m³ 3 A photovoltaic laminate 11, which is fixed by a bottom snap-fit, is installed in a rectangular pressure reactor 1. The shell of the reactor 1 is made of alloy material and lined with PTFE. 120L of tetrahydrofuran, 40L of toluene and 1760g of ionic liquid catalyst are added. The ionic liquid catalyst is prepared by mixing TEA-Cl, ZnCl2 and NaOTf in a molar ratio of 1:1.2:1. The dynamic circulation spray system is turned on so that the mixed solution collected at the bottom of the reactor is first filtered by an online filter and then transported to the upper nozzle by a circulation pump. The reaction is carried out at 120℃ and 1.0MPa for 4h under the condition of circulation flow rate of 280L / min.
[0089] S3. Sorting: After the reaction is completed, open the reactor, release the bottom limit and manually pick up the complete cover glass and silicon solar cell, spray them with anhydrous ethanol and rinse them with n-hexane in sequence, and vacuum dry them at 60℃ and 0.03MPa for 2 hours to obtain reusable cover glass and silicon solar cell.
[0090] S4. Filtration and separation: The reaction mixture is filtered through a 20μm ceramic membrane to recover the metal concentrate. After standing and separating, the organic phase is recovered. The metal concentrate is selectively leached, precipitated and electrolyzed to obtain high-purity silver, high-purity copper and high-purity aluminum. The organic phase is distilled at 0.05MPa and 80℃~160℃ to obtain liquid hydrocarbon components.
[0091] S5. Solvent recycling and catalytic system regeneration: The tetrahydrofuran and toluene recovered in step S4 are returned to step S2 for use; the ionic liquid phase is volatilized at 85°C and 0.03 MPa, and then a small amount of zinc chloride is added and returned to step S2.
[0092] In this embodiment, the liquid hydrocarbon yield is approximately 49.8 wt%, and the recovery rates of silver, aluminum, and copper are approximately 93.6%, 88.5%, and 90.2%, respectively.
[0093] Example 5: A method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation, comprising the following steps:
[0094] S1. Pre-treatment of retired photovoltaic panels: Take retired double-glass crystalline silicon photovoltaic modules with POE as the main encapsulating film. After disassembly, retain the whole laminate with a size of approximately 1956mm×991mm and including front and rear glass. Remove surface dust with 40℃ deionized water and brushing. Then spray with 95% ethanol and dry under 60℃ hot air to obtain photovoltaic laminate 11.
[0095] S2, Chemical degradation of photovoltaic film: To a volume of 2m³ 3 A photovoltaic laminate 11, which is fixed by a bottom snap-fit, is installed in a rectangular pressure reactor 1. The shell of the reactor 1 is made of alloy material and lined with PTFE. 80L of dimethylcyclohexylamine, 80L of mixed xylene and 1920g of ionic liquid catalyst are added. The ionic liquid catalyst is prepared by mixing [Bmim]Cl, AlCl3 and NaOTf in a molar ratio of 4:5:1. The dynamic circulation spray system is turned on so that the mixed solution collected at the bottom of the reactor is first filtered by an online filter and then transported to the upper nozzle by a circulation pump. The reaction is carried out at 130℃ and 1.1MPa for 3.5h under the condition of circulation flow rate of 320L / min.
[0096] S3. Sorting: After the reaction is completed, open the reactor, release the bottom limit and manually pick up the complete cover glass and silicon solar cell, spray them with anhydrous ethanol and rinse them with n-hexane in sequence, and vacuum dry them at 60℃ and 0.03MPa for 2 hours to obtain reusable cover glass and silicon solar cell.
[0097] S4. Filtration and separation: After filtration and settling, the reaction mixture is used to recover the organic phase and separate the metal concentrate. The metal concentrate is selectively leached, precipitated and electrolyzed to obtain high-purity silver, high-purity copper and high-purity aluminum. After solvent removal, the organic phase is distilled at 0.04 MPa and 85℃~175℃ to obtain liquid hydrocarbon components.
[0098] S5. Solvent recycling and catalytic system regeneration: The solvent recovered in step S4 is returned to step S2 for use; the ionic liquid phase is recycled after pre-devouring, acid replenishment and filtration.
[0099] In this embodiment, the liquid hydrocarbon yield is approximately 53.6 wt%, and the recovery rates of silver, aluminum, and copper are approximately 95.1%, 89.4%, and 91.6%, respectively.
[0100] Example 6: A method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation, comprising the following steps:
[0101] S1. Pre-treatment of retired photovoltaic panels: Take retired single-glass crystalline silicon photovoltaic modules with EVA / POE co-extrusion system as the main encapsulation film. First, manually remove the aluminum frame and junction box, leaving the whole laminate with a size of about 1956mm×991mm. Remove surface dust with 40℃ deionized water and brushing. Then spray with 95% ethanol and dry in 60℃ hot air to obtain photovoltaic laminate 11.
[0102] S2, Chemical degradation of photovoltaic film: To a volume of 2m³ 3 A photovoltaic laminate 11, which is fixed by a bottom snap-fit, is installed in a rectangular pressure reactor 1. The shell of reactor 1 is made of alloy material and lined with PTFE. 60L of benzyl alcohol, 100L of mixed xylene and 1920g of ionic liquid catalyst are added. The ionic liquid catalyst is prepared by mixing TEA-Cl, AlCl3 and NaOTf in a molar ratio of 1:1.2:0.5. The dynamic circulation spray system is turned on so that the mixed solution collected at the bottom of the reactor is first filtered by an online filter and then transported to the upper nozzle by a circulation pump. The reaction is carried out at 155℃ and 1.5MPa for 3h under the condition of circulation flow rate of 280L / min.
[0103] S3. Sorting: After the reaction is completed, open the reactor, release the bottom limit and manually pick up the complete cover glass and silicon solar cell, spray them with anhydrous ethanol and rinse them with n-hexane in sequence, and vacuum dry them at 60℃ and 0.03MPa for 2 hours to obtain reusable cover glass and silicon solar cell.
[0104] S4. Filtration and separation: The reaction mixture is hot-filtered and then allowed to stand at 45°C to separate into layers; the metal concentrate obtained by filtration is selectively leached, precipitated and electrolyzed to obtain high-purity silver, high-purity copper and high-purity aluminum; the organic phase is desolvated under reduced pressure and distilled at 0.03MPa and 95°C~190°C to obtain liquid hydrocarbon components.
[0105] S5. Solvent recycling and catalytic system regeneration: The solvent recovered in step S4 is returned to step S2; the ionic liquid phase is pre-devoured at 95°C and dehydrated by molecular sieve adsorption before being recycled.
[0106] In this embodiment, the liquid hydrocarbon yield is approximately 60.1 wt%, and the recovery rates of silver, aluminum, and copper are approximately 94.6%, 89.1%, and 90.8%, respectively.
[0107] Example 7: A method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation, comprising the following steps:
[0108] S1. Pre-treatment of retired photovoltaic panels: Take retired single-glass crystalline silicon photovoltaic modules with EVA as the main encapsulant film and fluorine-containing composite backsheet as the backsheet. First, manually remove the aluminum frame and junction box, leaving the whole laminate with a size of approximately 1956mm×991mm. Remove surface dust with 40℃ deionized water and brushing. Then, spray with 95% ethanol and dry under 60℃ hot air to obtain photovoltaic laminate 11.
[0109] S2, Chemical degradation of photovoltaic film: To a volume of 2m³ 3 A photovoltaic laminate 11, which is fixed by a bottom snap-fit, is installed in a rectangular pressure reactor 1. The shell of the reactor 1 is made of alloy material and lined with PTFE. 80L of o-dichlorobenzene, 80L of toluene and 1920g of ionic liquid catalyst are added. The ionic liquid catalyst is prepared by mixing [Bmim]Cl, FeCl3 and NaOTf in a molar ratio of 1:1.5:0.5. The dynamic circulation spray system is turned on so that the mixed solution collected at the bottom of the reactor is first filtered by an online filter and then transported to the upper nozzle by a circulation pump. The reaction is carried out at 160℃ and 1.6MPa for 3.5h under the condition of circulation flow rate of 320L / min.
[0110] S3. Sorting: After the reaction is completed, open the reactor, release the bottom limit and manually pick up the complete cover glass and silicon solar cell, spray them with anhydrous ethanol and rinse them with n-hexane in sequence, and vacuum dry them at 60℃ and 0.03MPa for 2 hours to obtain reusable cover glass and silicon solar cell.
[0111] S4. Filtration and separation: The reaction mixture is filtered, settled and phase separated; the organic phase is distilled at 0.03 MPa and 100℃~200℃ to obtain liquid hydrocarbon components, while recovering metal concentrates containing silver, aluminum and copper; the metal concentrates are selectively leached, precipitated and electrolyzed to obtain high-purity silver, high-purity copper and high-purity aluminum.
[0112] S5. Solvent recycling and catalytic system regeneration: The solvent recovered in step S4 is returned to step S2; the ionic liquid phase is recycled after pre-devouring, addition of ferric chloride, and filtration.
[0113] In this embodiment, the liquid hydrocarbon yield is approximately 45.4 wt%, and the recovery rates of silver, aluminum, and copper are approximately 91.8%, 87.6%, and 89.5%, respectively.
[0114] Example 8: A method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation, comprising the following steps:
[0115] S1. Pre-treatment of retired photovoltaic panels: Take retired single-glass crystalline silicon photovoltaic modules with EVA as the main encapsulating film and PET composite backsheet as the backsheet. First, manually remove the aluminum frame and junction box, leaving the whole laminate with a size of approximately 1956mm×991mm. Remove surface dust with 40℃ deionized water and brushing. Then, spray with 95% ethanol and dry in 60℃ hot air to obtain photovoltaic laminate 11.
[0116] S2, Chemical degradation of photovoltaic film: To a volume of 2m³ 3 A photovoltaic laminate 11, which is fixed by a bottom snap-fit, is installed in a rectangular pressure reactor 1. The shell of the reactor 1 is made of alloy material and lined with PTFE. 80L of trichloroethylene, 80L of mixed xylene and 1600g of ionic liquid catalyst are added. The ionic liquid catalyst is prepared by mixing [Bmim]Cl and AlCl3 in a molar ratio of 1:1.5. The dynamic circulation spray system is turned on so that the mixed solution collected at the bottom of the reactor is first filtered by an online filter and then transported to the upper nozzle by a circulation pump. The reaction is carried out at 150℃ and 1.4MPa for 3h under the condition of circulation flow rate of 280L / min.
[0117] S3. Sorting: After the reaction is completed, open the reactor, release the bottom limit and manually pick up the complete cover glass and silicon solar cell, spray them with anhydrous ethanol and rinse them with n-hexane in sequence, and vacuum dry them at 60℃ and 0.03MPa for 2 hours to obtain reusable cover glass and silicon solar cell.
[0118] S4. Filtration and separation: The reaction mixture is filtered through a 20μm ceramic membrane and allowed to stand to separate into layers. The metal concentrate is recovered. The metal concentrate is selectively leached, precipitated and electrolyzed to obtain high-purity silver, high-purity copper and high-purity aluminum. The organic phase is distilled at 0.04MPa and 90℃~185℃ to obtain liquid hydrocarbon components.
[0119] S5. Solvent recycling and catalytic system regeneration: Trichloroethylene and mixed xylene recovered in step S4 are returned to step S2 for use; the ionic liquid phase is devolatilized at 90°C and 0.03 MPa and anhydrous aluminum trichloride is added before returning to step S2.
[0120] In this embodiment, the liquid hydrocarbon yield was approximately 52.8 wt%, and the recovery rates of silver, aluminum, and copper were approximately 92.9%, 88.3%, and 90.1%, respectively.
[0121] Example 9: A method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation, comprising the following steps:
[0122] S1. Pre-treatment of retired photovoltaic panels: Take slightly aged retired monoglass crystalline silicon photovoltaic modules with EVA as the main encapsulating film. First, manually remove the aluminum frame and junction box, leaving the whole laminate with a size of approximately 1956mm×991mm. Remove surface dust with 40℃ deionized water and brushing. Then, spray with 95% ethanol and dry under 60℃ hot air to obtain photovoltaic laminate 11.
[0123] S2, Chemical degradation of photovoltaic film: To a volume of 2m³ 3 A photovoltaic laminate 11, which is fixed by a bottom snap-fit, is installed in a rectangular pressure reactor 1. The shell of the reactor 1 is made of alloy material and lined with PTFE. 80L of anisole, 80L of mixed xylene, and 6wt% concentrated sulfuric acid (H2SO4) based on the mass of the mixed solution are added. The dynamic circulation spray system is turned on so that the mixed solution collected at the bottom of the reactor is first filtered by an online filter and then transported to the upper nozzle by a circulation pump. The reaction is carried out at 138℃ and 1.2MPa for 2.5h under the condition of circulation flow rate of 320L / min.
[0124] S3. Sorting: After the reaction is completed, open the reactor, release the bottom limit and manually pick up the complete cover glass and silicon solar cell, spray them with anhydrous ethanol and rinse them with n-hexane in sequence, and vacuum dry them at 60℃ and 0.03MPa for 2 hours to obtain reusable cover glass and silicon solar cell.
[0125] S4. Filtration and Separation: The reaction mixture was thermally filtered through a 20μm ceramic membrane to obtain a metal-enriched residue and a filtrate. The filtrate was allowed to stand at 45℃ for 1 hour to separate into an upper organic phase and a lower sulfuric acid phase. The organic phase was desolventized under reduced pressure and then distilled at 0.04MPa and 85℃~175℃ to obtain a liquid hydrocarbon component. The metal-enriched residue and the sulfuric acid phase were combined and 0.15mol / L ferric sulfate was added. The mixture was leached at room temperature for 2 hours. After filtration to remove impurities, silver was first recovered by precipitation with sodium chloride. Then, copper was recovered by electrolysis of the mother liquor and aluminum was recovered by precipitation by adjusting the pH.
[0126] S5. Solvent recycling and catalytic system regeneration: The anisole and mixed xylene recovered in step S4 are returned to step S2 for use; the sulfuric acid phase is de-idered under reduced pressure to remove the entrained organic solvent, and a small amount of concentrated sulfuric acid and hydrogen peroxide are added before returning to step S2 for recycling.
[0127] In this embodiment, the liquid hydrocarbon yield is approximately 57.6 wt%, and the recovery rates of silver, aluminum, and copper are approximately 89.8%, 90.5%, and 96.3%, respectively.
[0128] Example 10: A method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation, comprising the following steps:
[0129] S1. Pre-treatment of retired photovoltaic panels: Take heavily aged retired monoglass crystalline silicon photovoltaic modules with EVA as the main encapsulating film. First, manually remove the aluminum frame and junction box, leaving the whole laminate with a size of approximately 1956mm×991mm. Remove surface dust with 40℃ deionized water and brushing. Then, spray with 95% ethanol and dry under 60℃ hot air to obtain photovoltaic laminate 11.
[0130] S2, Chemical degradation of photovoltaic film: To a volume of 2m³ 3 A rectangular pressure-resistant reactor 1 is fitted with a photovoltaic laminate 11 that is fixed by a bottom snap-fit. The shell of the reactor 1 is made of alloy material and lined with PTFE. 100L of trichloroethylene, 40L of mixed xylene, 20L of 4mol / L nitric acid and 960g of ionic liquid catalyst are added. The ionic liquid catalyst is prepared by mixing [Bmim]Cl and AlCl3 in a molar ratio of 1:1.2. Nitric acid serves as both an inorganic solvent and an acidic catalyst. The dynamic circulating spray system is turned on so that the mixed solution collected at the bottom of the reactor is first filtered by an online filter and then pumped to the upper nozzle by a circulating pump. The reaction is carried out at 135℃ and 1.2MPa for 3h under a circulation flow rate of 300L / min.
[0131] S3. Sorting: After the reaction is completed, open the reactor, release the bottom limit and manually pick up the complete cover glass and silicon solar cell, spray them with anhydrous ethanol and rinse them with n-hexane in sequence, and vacuum dry them at 60℃ and 0.03MPa for 2 hours to obtain reusable cover glass and silicon solar cell.
[0132] S4. Filtration and separation: The reaction mixture was filtered through a 20μm ceramic membrane and allowed to stand to separate into layers, yielding an organic phase, a nitric acid phase, and an ionic liquid enriched phase. The organic phase was distilled at 0.04MPa and 90℃~180℃ to obtain a liquid hydrocarbon component. The nitric acid phase was filtered through a 1μm filter membrane to remove impurities. Sodium chloride was added to precipitate and recover silver. The mother liquor was electrolyzed to recover copper, and aluminum was recovered by precipitating by adjusting the pH.
[0133] S5. Solvent recycling and catalytic system regeneration: Trichloroethylene and mixed xylene recovered in step S4 are returned to step S2 for use; the ionic liquid enriched phase is pre-devoured at 90°C and 0.03 MPa and a small amount of anhydrous aluminum trichloride is added before returning to step S2; the nitric acid phase is returned to the metal leaching unit after acid replenishment.
[0134] In this embodiment, the liquid hydrocarbon yield was approximately 52.1 wt%, and the recovery rates of silver, aluminum, and copper were approximately 97.8%, 87.1%, and 91.4%, respectively.
[0135] Example 11: A method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation, comprising the following steps:
[0136] S1. Pre-treatment of retired photovoltaic panels: Take retired double-glass crystalline silicon photovoltaic modules with POE as the main encapsulating film. After disassembly, retain the whole laminate with a size of approximately 1956mm×991mm and including front and rear glass. Remove surface dust with 40℃ deionized water and brushing. Then spray with 95% ethanol and dry under 60℃ hot air to obtain photovoltaic laminate 11.
[0137] S2, Chemical degradation of photovoltaic film: To a volume of 2m³ 3 A rectangular pressure-resistant reactor 1 is fitted with a photovoltaic laminate 11 that is fixed by a bottom snap-fit. The shell of the reactor 1 is made of alloy material and lined with PTFE. 80L of d-limonene and 2wt% of supercritical isopentane based on the mass of d-limonene are added, along with 1760g of ionic liquid catalyst. The ionic liquid catalyst is prepared by mixing TEA-Cl, ZnCl2 and NaOTf in a molar ratio of 1:1.2:1. The dynamic circulating spray system is turned on so that the mixed solution collected at the bottom of the reactor is first filtered by an online filter and then pumped to the upper nozzle by a circulating pump. The reaction is carried out at 155℃, 3.8MPa and a circulation flow rate of 280L / min for 3h.
[0138] S3. Sorting: After the reaction is completed, open the reactor, release the bottom limit and manually pick up the complete cover glass and silicon solar cell, spray them with anhydrous ethanol and rinse them with n-hexane in sequence, and vacuum dry them at 60℃ and 0.03MPa for 2 hours to obtain reusable cover glass and silicon solar cell.
[0139] S4. Filtration and separation: The reaction mixture is filtered, allowed to stand, and distilled under reduced pressure, while recovering the metal concentrate. The metal concentrate is selectively leached, precipitated, and electrolyzed to obtain high-purity silver, high-purity copper, and high-purity aluminum. The organic phase is distilled at 0.04 MPa and 90℃~190℃ to obtain liquid hydrocarbon components.
[0140] S5. Solvent recycling and catalytic system regeneration: The d-limonene and supercritical isopentane recovered in step S4 are returned to step S2 for reuse; the ionic liquid phase is recycled after pre-devouring, addition of zinc chloride, and filtration.
[0141] In this embodiment, the liquid hydrocarbon yield is approximately 50.7 wt%, and the recovery rates of silver, aluminum, and copper are approximately 93.2%, 88.8%, and 90.7%, respectively.
[0142] Example 12: A method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation, comprising the following steps:
[0143] S1. Pre-treatment of retired photovoltaic panels: Take a hybrid retired photovoltaic module containing EVA laminate and POE laminate, remove the frame and junction box respectively, retain the whole laminate with a size of approximately 1956mm×991mm, and perform pre-treatment to obtain photovoltaic laminate 11.
[0144] S2, Chemical degradation of photovoltaic film: To a volume of 2m³ 3 A photovoltaic laminate 11, which is fixed by a bottom snap-fit, is installed in a rectangular pressure reactor 1. The shell of the reactor 1 is made of alloy material and lined with PTFE. 80L of light naphtha, 80L of mixed xylene and 1920g of ionic liquid catalyst are added. The ionic liquid catalyst is prepared by mixing [Bmim]Cl, AlCl3 and NaOTf in a molar ratio of 4:5:1. The dynamic circulation spray system is turned on so that the mixed solution collected at the bottom of the reactor is first filtered by an online filter and then transported to the upper nozzle by a circulation pump. The reaction is carried out at 150℃ and 1.5MPa for 3h under the condition of circulation flow rate of 320L / min.
[0145] S3. Sorting: After the reaction is completed, the bottom limit is removed, and the obtained product is manually sorted and filtered. It is then sprayed with anhydrous ethanol and washed with n-hexane in sequence, and vacuum dried at 60℃ and 0.03MPa for 2h to obtain reusable cover glass and silicon solar cells.
[0146] S4. Filtration and separation: The filtrate is allowed to stand and separate into layers to obtain an organic phase and an ionic liquid phase; after the solvent is removed from the organic phase, it is distilled at 0.04 MPa and 90℃~185℃ to obtain a liquid hydrocarbon component, and the metal concentrate is recovered; the metal concentrate is selectively leached, precipitated and electrolyzed to obtain high-purity silver, high-purity copper and high-purity aluminum.
[0147] S5. Solvent recycling and catalytic system regeneration: The solvent recovered in step S4 is returned to step S2 for recycling; the ionic liquid phase is pre-devoured at 95°C and 0.03 MPa, and then returned to step S2 after being supplemented with anhydrous aluminum trichloride and filtered.
[0148] In this embodiment, the liquid hydrocarbon yield was approximately 59.3 wt%, and the recovery rates of silver, aluminum, and copper were approximately 94.3%, 89.5%, and 91.4%, respectively.
[0149] refer to Figure 4-6The method provided by this invention is adaptable to EVA, POE, EVA / POE co-extruded films, and decommissioned photovoltaic laminates with different backsheet structures. Organic solvents and inorganic solvents such as nitric acid can be used to dissolve the photovoltaic film, while ionic liquids, concentrated sulfuric acid, and nitric acid can all serve as catalytic systems for photovoltaic film degradation. Under relatively mild conditions, a high rate of complete recovery of the cover glass and silicon solar cells can be achieved, along with a high recovery rate of metals such as silver, aluminum, and copper, while maintaining good recyclability of the solvent and catalytic system.
[0150] Example 13: A method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation, comprising the following steps:
[0151] S1. Pre-treatment of decommissioned photovoltaic panels:
[0152] The retired photovoltaic modules are disassembled, cleaned and sorted to remove directly recyclable parts, resulting in photovoltaic laminate 11. The directly recyclable parts include aluminum frames, junction boxes or junction frames.
[0153] S2, Chemical degradation of photovoltaic film:
[0154] The photovoltaic laminate 11 is fixed to the limiting device at the bottom of the reactor 1. A mixed solution consisting of solvent and catalyst is added to the reactor 1. Under the action of a dynamic fluid circulation system, the solution is dissolved and catalytically degraded at 60~200℃ and 0.1MPa~5MPa for 0.1~8h to obtain a complete cover glass, silicon solar cell, liquid hydrocarbon product and a reaction mixture containing solvent, catalyst and soluble metal components.
[0155] S3, Sorting:
[0156] The reaction products were sorted, and the glass plate and silicon solar cell were removed. After cleaning and vacuum drying, reusable cover glass and silicon solar cell were obtained.
[0157] S4, Filtration and Separation:
[0158] The heterogeneous mixture is separated to remove solid impurities and undissolved particles, and the metal concentrates or metal leachates of silver, aluminum, copper and solder are recovered. The reaction mixture is allowed to stand at 20℃~90℃ to separate into layers, yielding an organic phase and an ionic liquid phase or an acidic catalytic phase. The organic phase is desolventized and then distilled to obtain a liquid hydrocarbon component. The metal concentrates or metal leachates are separated by hydrometallurgical methods, and then subjected to filtration to remove impurities, selective precipitation and / or electrolysis to obtain high-purity silver, high-purity aluminum and high-purity copper.
[0159] S5, Solvent recycling and catalytic system regeneration:
[0160] The removed solvent is returned to step S2 for recycling; the ionic liquid phase or acidic catalytic phase is regenerated and then returned to step S2 for recycling. This invention integrates pretreatment, solvent dissolution, chemical degradation, sorting, filtration separation, hydrometallurgical recovery, and solvent / catalytic system recycling into one system. It can systematically address multiple indicators such as the recovery of intact cover glass and silicon solar cells, high-purity recovery of metals such as silver, aluminum, and copper, acquisition of liquid hydrocarbon products, and closed-loop reuse of media, thus improving the problem of the disconnect between "decapsulation" and "high-value recovery" in existing technologies.
[0161] Example 14: Based on Example 13, with reference to... Figure 2 , Figure 3 The reactor 1 is a rectangular or near-rectangular pressure-resistant reactor, and operates in conjunction with a dynamic circulating spray system. The dynamic circulating spray system includes a collection zone, a filter 5, a circulating pump 6, and a spray device. The spray device includes a bottom manifold 4 at the bottom of the reactor 1, a top manifold 3 at the top of the reactor 1, and nozzles 2 at the outlet of the top manifold 3. The bottom manifold 4 is connected to the circulating pump 6 and the top manifold 3 sequentially through the filter 5. The outer shell of the reactor 1 is made of a corrosion-resistant alloy material, including any one of 316L stainless steel or Hastelloy. The inner wall of the reactor 1 is lined with a PTFE liner 10 and equipped with a jacketed heating, pressure monitoring, and inert gas protection device. When processing the entire laminated component after removing the frame and junction box, the volume of the reactor 1 is 0.1-4 m³; the corresponding initial liquid volume of the mixed solution is 80 L~180 L. The top surface of reactor 1 is equipped with a sealing cover 7, and the bottom inner side of reactor 1 is equipped with a limiting and fixing device, which includes a buckle 9, a pressure strip, a positioning pin 12, and a guide frame 8. The buckle 9 fixes the photovoltaic laminate 11 after the aluminum frame, junction box, or junction frame has been removed through the pressure strip and the positioning pin 12. A photovoltaic laminate load-bearing block 13 is set inside the guide frame 8 to support the photovoltaic laminate 11. The bottom of the guide frame 8 contacts the bottom inner side of reactor 1 through the guide frame load-bearing block 14. The dynamic circulating spray system first introduces the solvent / ionic liquid mixture collected at the bottom of reactor 1 into the filter 5 to remove metal fragments, weld strips, and incompletely separated particles, and then transports it to the nozzle 2 on the upper layer of reactor 1 through the circulating pump 6 and the top manifold 3, thereby forming a continuously renewed solvent / catalyst liquid film on the surface of the photovoltaic laminate 11 to achieve mass transfer, heat transfer, and stirring. This invention, through the synergistic effect of a rectangular pressure-resistant reactor and a dynamic circulating spray system, can still improve the renewal rate and penetration uniformity of solvent and catalyst on the surface of laminated components without the presence of a stirring paddle in the reactor, shorten the encapsulant film treatment cycle, and reduce the risk of damage to glass and solar cells caused by localized excessive swelling, thereby facilitating the gentle and efficient dismantling of retired photovoltaic modules.
[0162] The above are merely preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation, characterized in that: Includes the following steps: S1. Pre-treatment of decommissioned photovoltaic panels: The retired photovoltaic modules are disassembled, cleaned and sorted to remove directly recyclable parts, resulting in photovoltaic laminates (11). The directly recyclable parts include aluminum frames, junction boxes or wiring frames. S2, Chemical degradation of photovoltaic film: The photovoltaic laminate (11) is fixed on the limiting device at the bottom of the reactor (1). A mixed solution of solvent and catalyst is added to the reactor (1). Under the action of the dynamic fluid circulation system, the solution is dissolved and catalytically degraded at room temperature to 200°C and 0.1MPa to 5MPa for 0.1 to 8 hours to obtain complete cover glass, silicon solar cell, liquid hydrocarbon product and reaction mixture containing solvent, catalyst and soluble metal components. S3, Sorting: The reaction products were sorted, and the glass plate and silicon solar cell were removed. After cleaning and vacuum drying, reusable cover glass and silicon solar cell were obtained. S4, Filtration and Separation: The heterogeneous mixture is separated to remove solid impurities and undissolved particles, and the metal concentrates or metal leachates of silver, aluminum, copper and solder are recovered. The reaction mixture is allowed to stand at 20℃~90℃ to separate into layers, yielding an organic phase and an ionic liquid phase or an acidic catalytic phase. The organic phase is desolventized and then distilled to obtain a liquid hydrocarbon component. The metal concentrates or metal leachates are separated by hydrometallurgical methods, and then subjected to filtration to remove impurities, selective precipitation and / or electrolysis to obtain high-purity silver, high-purity aluminum and high-purity copper. S5, Solvent recycling and catalytic system regeneration: The removed solvent is returned to step S2 for recycling; the ionic liquid phase or acidic catalytic phase is regenerated and then returned to step S2 for recycling.
2. The method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation according to claim 1, characterized in that: The disassembly in step S1 is carried out manually or by automated disassembly equipment. The automated disassembly equipment includes a frame disassembly unit, a junction box cutting unit, an appearance identification unit, and a laminate conveying unit. According to the component size and the specifications of the reactor (1), the photovoltaic laminate (11) after removing the frame is placed directly on the bottom limiting device of the reactor (1), or cut into laminate sheets of 10mm×10mm~2000mm×2000mm. The cleaning process adopts a combination of water washing and organic solvent washing to remove surface mud, dust, oil stains and residual adhesive on the back.
3. The method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation according to claim 2, characterized in that: The solvent in step S2 is selected individually or in combination according to the photovoltaic film type, degree of crosslinking and backsheet configuration; the solvent includes one or more of aromatic hydrocarbon solvents, alicyclic hydrocarbon solvents, halogenated hydrocarbon solvents, terpene solvents, ether solvents, alcohol solvents, ketone solvents, supercritical alkane solvents, inorganic acid solvents and oxidizing mixed reagents.
4. The method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation according to claim 3, characterized in that: The solvent is selected based on the solubility parameter matching relationship between the photovoltaic film and the solvent. For EVA film, one or more of toluene, xylene, mixed xylene, trichloroethylene, o-dichlorobenzene and d-limonene are selected. For POE film, a mixed solvent of tetrahydrofuran, dimethylcyclohexylamine, d-limonene and aromatic hydrocarbons, or a supercritical alkane and organic co-solvent compound system are selected. For EVA / POE co-extruded film and encapsulation layer after long-term service aging, a mixed solvent system of terpenes / aromatic hydrocarbons, aromatic hydrocarbons / alcohols, and ethers / aromatic hydrocarbons is selected. For photovoltaic laminates (11) that need to simultaneously promote the dissolution of metal grid lines or remove difficult-to-treat backsheets, nitric acid and concentrated sulfuric acid are added to the above organic solvent system, or a mixed reagent of hydrofluoric acid and hydrogen peroxide is used in the staged treatment.
5. The method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation according to claim 3, characterized in that: In step S2, an inorganic solvent is also added. The inorganic solvent is added as a whole, added in stages, or selectively leached later. When the goal is to recover the complete cover glass, the inorganic solvent is used to leach the silicon solar cells or metal concentrates after the glass plate is removed. When the goal is to rapidly dissolve metals, the inorganic solvent is added in the later stage of the reaction in step S2 by spraying or circulating, thereby promoting the deadhesion of the film interface and allowing silver, aluminum, and copper to enter the liquid phase.
6. The method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation according to claim 1, characterized in that: The reactor (1) is a rectangular or near-rectangular pressure-resistant reactor. The reactor (1) operates in conjunction with a dynamic circulating spray system. The dynamic circulating spray system includes a collection area, a filter (5), a circulating pump (6), and a spray device. The spray device includes a bottom manifold (4) at the bottom of the reactor (1), a top manifold (3) at the top of the reactor (1), and a nozzle (2) at the outlet of the top manifold (3). The bottom manifold (4) is connected to the circulating pump (6) and the top manifold (3) in sequence through the filter (5). The outer shell of the reactor (1) is made of corrosion-resistant alloy material, including any one of 316L stainless steel and Hastelloy. The inner wall of the reactor (1) is lined with PTFE (10) and equipped with a jacketed heating, pressure monitoring, and inert gas protection device. When processing the whole-plate laminate after removing the frame and junction box, the volume of the reactor (1) is 0.1-4m³. 3 The initial liquid volume of the corresponding mixed solution is 80L~180L; a limiting and fixing device is provided on the inner bottom of the reactor (1). The limiting and fixing device includes a buckle (9), a pressure strip, a positioning pin (12), and a guide frame (8) to fix the photovoltaic laminate (11) after the aluminum frame, junction box or junction frame is removed; the dynamic circulating spray system first introduces the solvent / ionic liquid mixture collected at the bottom of the reactor (1) into the filter (5) to remove metal fragments, welding strips and incompletely separated particles, and then transports it to the nozzle (2) on the upper layer of the reactor (1) through the circulating pump (6) and the top manifold (3), thereby forming a continuously renewed solvent / catalyst liquid film on the surface of the photovoltaic laminate (11) to achieve mass transfer, heat transfer and stirring.
7. The method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation according to claim 1, characterized in that: The sorting in step S3 can be completed by manual sorting or mechanical clamping; for the obtained complete cover glass and complete silicon solar cells, anhydrous ethanol, isopropanol, n-hexane or a mixture thereof are used for spray cleaning to remove residual organic matter and catalyst. Subsequently, the material is vacuum dried at 40℃~90℃ for 0.5~6 hours to obtain a recyclable component that can be directly used in subsequent remanufacturing or material reuse processes.
8. The method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation according to claim 1, characterized in that: The catalyst in step S2 is an ionic liquid catalyst, a eutectic solvent catalyst, and / or an acidic catalyst; the ionic liquid catalyst is obtained by mixing a cationic reagent and anionic reagent in a molar ratio of 1:(0.5~7); the amount of ionic liquid catalyst is 1%~50% of the organic encapsulation material in the photovoltaic laminate (11), and the acidic catalyst is added at 0.5%~20% of the mass of the mixed solution; the catalyst is prepared in advance before the reaction, or generated in situ in the reactor or added in stages; The cation reagent is one or more of imidazole salts, pyridine salts, quaternary ammonium salts, and quaternary phosphine salts; imidazole salts include 1-butyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium chloride, 1-propyl-3-methylimidazolium chloride, and 1-octyl-3-methylimidazolium chloride; pyridine salts include benzylpyridine salt and butylpyridine salt; quaternary ammonium salts include triethylammonium chloride, tetraethylammonium salt, benzyltrimethylammonium salt, and tetrabutylammonium salt; and quaternary phosphine salts include trioctylmethylphosphine salt. The anionic reagent is one or more of a metal halide, a metal halide, or a fluorosulfonate; the metal halides include anhydrous aluminum trichloride, anhydrous ferric chloride, cuprous chloride, gallium trichloride, and stannous chloride; the metal halide includes zinc chloride, sodium tetrafluoroborate, lithium hexafluorophosphate, potassium hexafluorophosphate, and potassium hexafluoroantimonate; the fluorosulfonate includes sodium trifluoromethanesulfonate. The acid catalyst is one or more of concentrated sulfuric acid, trifluoromethanesulfonic acid, methanesulfonic acid, p-toluenesulfonic acid, and chlorosulfonic acid. The acid catalyst can be used alone or in combination with ionic liquid catalyst. Concentrated sulfuric acid can promote the deacetylation of vinyl acetate units and the loosening of cross-linked networks in EVA, while trifluoromethanesulfonic acid, as a strong Brønsted acid, can increase the activation rate of polar groups in the aged film. Both are beneficial to the chain scission degradation and interfacial deadhesion of photovoltaic films. The reaction conditions are 100℃~170℃, 0.5MPa~2.5MPa, and 0.5~5h. The eutectic solvent catalyst is a eutectic system (also known as a deep eutectic solvent) composed of amide compounds and aluminochloroaluminate; amide compounds are organic compounds containing amide groups (–CONH–) in their molecules, selected from one or more of acetamide, propionamide, butyramide, hexamethylenetetramine, benzamide, nicotinamide, urea, caprolactam, and N-methylacetamide; aluminochloroaluminate is provided by anhydrous aluminum trichloride, or by anhydrous aluminum trichloride combined with a chlorine donor to form aluminochloroaluminate anion; the chlorine donor is one or more of choline chloride, ammonium chloride, potassium chloride, and sodium chloride; the amide compound and anhydrous aluminum trichloride... The molar ratio of aluminum chloride is 1:(0.5~3); when a chlorine donor is used in combination, the molar ratio of amide compound, anhydrous aluminum trichloride and chlorine donor is 1:(0.5~3):(0.01~1); the amount of eutectic solvent catalyst is 1%~50% based on the mass of organic encapsulant in photovoltaic laminate; the eutectic solvent catalyst can be prepared in advance and added to the reaction system, or the amide compound and anhydrous aluminum trichloride can be added to the reactor separately or together to generate the eutectic phase in situ; or anhydrous aluminum trichloride or amide compound can be added in stages according to the reaction process to maintain catalytic activity and solvent characteristics.
9. The method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation according to claim 1, characterized in that: In step S4, the solvent removal and distillation pressure of the organic phase is 0.01~0.08MPa, and the distillation temperature is 60℃~220℃. The liquid hydrocarbon can be cut into C5~C12 light fractions, C13~C18 medium fractions and C19+ heavy fractions. The light fractions are used as components for blending recycled gasoline, the medium fractions are used as precursor components for diesel or sustainable aviation fuel, and the heavy fractions are returned to the cracking unit or used as chemical feedstocks, or returned to step S2 to replenish the organic solvent. In step S4, the solid residue obtained by filtration includes solder ribbon fragments, silver paste strips, aluminum backing fragments, copper strips, backing plate particles, and inorganic fine particles. These are further processed by sieving, magnetic separation, eddy current separation, and selective leaching to obtain silver, aluminum, copper, and solder metal enrichments. For the metals that enter the liquid phase, a hydrometallurgical method is used for recovery: first, selective leaching is performed using nitric acid, concentrated sulfuric acid, sulfuric acid / iron salt system, or a mixture of hydrofluoric acid and hydrogen peroxide; then, impurities are removed by plate and frame filtration or membrane filtration; and finally, high-purity silver, high-purity aluminum, and high-purity copper are obtained through selective precipitation, displacement, electrolysis, or ion exchange. The mixture obtained after the catalytic degradation reaction contains liquid hydrocarbon products, solvent, ionic liquid catalyst and suspended solids. After standing at 20℃~60℃ for 0.1~5h, an upper organic phase and a lower ionic liquid phase, or an intermediate transition phase, are formed. The quality of the clear liquid is further improved by hot filtration, centrifugation or demulsification. The organic phase after solvent removal is subjected to vacuum distillation to obtain narrow boiling range liquid hydrocarbon components. When the system uses inorganic acid or a mixed reagent containing hydrogen peroxide, the acidic liquid phase obtained from phase separation is directly introduced into the metal recovery unit as the metal leaching solution without the need for additional liquid replacement. After filtering to remove silicon powder, glass powder and backplate particles, selective precipitation, electrolysis or crystallization recovery is carried out in sequence according to the standard potential difference of silver, aluminum and copper.
10. A method for high-value recycling of decommissioned photovoltaic modules based on chemical degradation according to claim 1, characterized in that: The regeneration in step S5 includes one or more of the following: pre-devouring, acidity recovery, and impurity removal; Pre-devouring is the process of removing residual solvents and low-boiling organics from the ionic liquid phase under reduced pressure and / or inert gas protection. Acidity recovery involves adding metal halides, fluorosulfonate salts, or organic halides to the pre-devoured ionic liquid system to restore Lewis acidity and Brønsted acid sites. Impurity removal involves removing coke particles, inorganic particles, and polar byproducts through filtration separation and / or adsorption purification. When the acidity of the pre-devoured ionic liquid system decreases due to changes in complexation equilibrium, hydrolysis, or consumption of acid sites during the reaction, anhydrous aluminum trichloride, zinc chloride, sodium trifluoromethanesulfonate, or an organohalogenated compound is added according to the system composition. The regenerated ionic liquid is then thermally filtered at 40℃~80℃ through a 1~20μm sintered metal or ceramic filter to remove coke particles and inorganic particles. Ionic liquids that meet the acidity and activity requirements are directly returned to step S2 for recycling. The total reuse rate of the recovered solvent and regenerated ionic liquid during the recycling process is not less than 85%. When concentrated sulfuric acid, trifluoromethanesulfonic acid or other acidic catalysts are used, regeneration includes removing organic solvents, adjusting acidity, adding oxidant and removing impurities; in the case of sulfuric acid system, hydrogen peroxide or iron salt is added to restore oxidizing property, and in the case of trifluoromethanesulfonic acid system, low-boiling components are removed by vacuum devolatilization and then directly reused or trifluoromethanesulfonic acid is added, and the total reuse rate of acidic catalyst phase is not less than 80%.
Citation Information
Patent Citations
Process for manufacturing silicon fertilizer by recycling waste photovoltaic panels
CN118083997A
Resource recycling method and system for photovoltaic module
CN119566027A
Method for recovering silicon powder from waste photovoltaic panel
CN121423353A